On the importance of moisture-resistant properties of concrete in the construction of current-limiting reactors of a substation - Rakhimov Р.В.; Mukataev Н. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2021)
Switchgears are an integral part of the energy industry of the Republic of Kazakhstan, which include substations, electrical installations, power transmission lines and other facilities. Currently, they are undergoing physical and moral wear and tear. The growth of production capacities of industry and the population emphasizes the need for intensive development of the energy complex using the technologies of the XXI century, while maintaining a technological balance between traditional energy and renewable energy sources [4]. The concept of development of the fuel and energy complex of the Republic of Kazakhstan until 2030 fully reflects these tasks and development approaches. In addition, the construction and reconstruction of distribution networks are due to the growth of a total load of consumers, which, even now, continues to increase rapidly. Concrete used in construction is an integral part of all types of construction and installation work. Thus, the concrete mixture used in the construction of energy facilities must have special properties and moisture-resistant characteristics, allowing you to solve specific energy problems, which include: reliability, durability, low electrical conductivity and other characteristics of concrete structures. High indicators of the above requirements are imposed in the places of installation of current-limiting reactors at electrical substations.